2021
DOI: 10.1177/14644207211032335
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing corrosion resistance and mechanical properties of dissimilar friction stir welded 5083-6061 aluminium alloys using external cooling environment

Abstract: Dissimilar friction stir welding of AA5083-AA6061 alloys in different cooling environments (air, liquid nitrogen, and water) was successfully employed as an alternative method to enhance corrosion resistance and mechanical properties. The evolution of microstructure, corrosion behavior, and mechanical properties of friction stir welded joints were studied using optical microscopy (OM), electron backscattered diffraction, scanning electron microscope, electrochemical workstation, and universal testing machine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…WCFSW with and without interlayer joints fractured in SZ due to improved hardness in HAZ. The shifting of water-cooled weld fracture location towards weld centre, that is, SZ was also observed by Sinhmar et al 41 and Kumar et al 44…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…WCFSW with and without interlayer joints fractured in SZ due to improved hardness in HAZ. The shifting of water-cooled weld fracture location towards weld centre, that is, SZ was also observed by Sinhmar et al 41 and Kumar et al 44…”
Section: Resultssupporting
confidence: 76%
“…WCFSW with and without interlayer joints fractured in SZ due to improved hardness in HAZ. The shifting of water-cooled weld fracture location towards weld centre, that is, SZ was also observed by Sinhmar et al 41 and Kumar et al 44 Generally, in metals, dimples indicate a ductile fracture, and these are formed when dislocations interact. Dislocations can easily slide, climb, and cross-slip during the initial stages of deformation.…”
Section: Mechanical Propertiessupporting
confidence: 68%
See 1 more Smart Citation
“…14 However, FSW process would be a better alternative for conventional processes when it is joining dissimilar materials. As an evidence sound welds for dissimilar Al-Al, 15 Mg-Mg, 16 Cu-Cu, 17 steel-steel 18 alloys and the combination of Al/Mg, 19 Al/Cu, 20 Al/steel, 21 Al/Ti, 22 Mg/steel, 23 Ti/steel, 24 Cu/steel 25 and stainless steel/superalloy 26 were reported.…”
Section: Introductionmentioning
confidence: 97%
“…They also found that galvanic coupling caused high corrosion density at the nugget zone. Out of all samples, less corrosion resistance was obtained for the sample welded at high rotation speed due to the formation of defects and insufficient material mixing [30][31][32].…”
Section: Open Circuit Potential (Ocp) Testmentioning
confidence: 99%